Relevance of multidrug resistance proteins for intestinal drug absorption in vitro and in vivo - Fricker, Gert; Miller, David S. (Pharmacology & toxicology, 2002)
Abstract: Multidrug resistance proteins (p-glycoprotein and mrps) are becoming increasingly important to explain the pharmacokinetics and action of drugs. Located in epithelial and endothelial cells of the gastrointestinal tract, liver, kidney, blood brain barrier, choroid plexus and other organs, they are critical determinants for the movement of a large number of commonly prescribed drugs across cellular barriers. Here we provide a brief overview of the role of multidrug resistance proteins in drug absorption from the gastrointestinal tract. We address the different types of multidrug resistance proteins involved, describe experimental models to study the influence of these proteins on transcellular transport and discuss the impact of multidrug resistance proteins on overall drug bioavailability in vivo.
Gesehen am 25.04.2017